VARIETIES OF RELIGIOUS COMMUNICATION: CULTURAL ANALYSIS - Петрушкевич, М. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article from position of cultural analysis the varieties of verbal and unverbal religious communication are examined.